Das Staatsarchiv Hamburg im Nationalsozialismus - Schmidt, Sarah (Veröffentlichungen aus dem Staatsarchiv der Freien und Hansestadt Hamburg, 2016)
Archives are places of history. They preserve testimonies of the past and make them accessible to the public, and also keep documents that bear witness to their own past.The influence of politics and ideology on archival activity was strongly developed during the period of National Socialism in Germany. Thus, the State Archives of Hamburg took a special position in the issue of the so-called "proofs of the Aryan" ("Ariernachweise") on account of its sources.The present work examines the past as well as the role of the state archives as well as the scientific archivists - Heinrich Reincke, Hans Kellinghusen, Erich von Lehe, and Kurt Detlev Möller - during the period of National Socialism by examination of the records, and considers the results on basis of current research.